Sarcopenia and Mortality in Critically Ill COVID-19 Patients - Fatima Al Zahra Yakti; Lana Abusalah; Vijay Ganji (Life, 2023)
COVID-19 can manifest as either asymptomatic or progressing to a severe phase in some patients, which may require hospitalization. These patients may experience dyspnea and hypoxia, leading to the development of acute respiratory distress syndrome. Studies have reported an increased risk of severe sarcopenia in COVID-19 patients during and after recovery. This narrative review aimed to summarize and synthesize available studies on the association between sarcopenia and mortality in critically ill COVID-19 patients. A total of 22 studies conducted on hospitalized COVID-19 patients were included in this review. Of those, 17 studies reported a direct association, while 5 studies showed no association between sarcopenia and mortality in severe COVID-19 patients. It is important to maintain muscle quality and quantity in defense against COVID-19. The measurement of lean muscle mass should be included in the risk assessment of severely ill COVID-19 patients as part of the therapy plan.